2016
DOI: 10.3389/fmicb.2016.00446
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium Subspecies paratuberculosis Infection Modifies Gut Microbiota under Different Dietary Conditions in a Rabbit Model

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) the causative agent of paratuberculosis, produces a chronic granulomatous inflammation of the gastrointestinal tract of ruminants. It has been recently suggested that MAP infection may be associated with dysbiosis of intestinal microbiota in ruminants. Since diet is one of the key factors affecting the balance of microbial populations in the digestive tract, we intended to evaluate the effect of MAP infection in a rabbit model fed a regular or high fiber di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 77 publications
(100 reference statements)
1
24
2
1
Order By: Relevance
“…Little is known about the presence of Anaerofustis (family Eubacteriaceae ) in intestinal communities. Arrazuria et al (2016) found an association between the presence of this genus in cecal samples collected from female rabbits and Mycobacterium avium paratuberculosis infection. Some Anaerofustis species could be involved in the fermentation of carbohydrates and glucose metabolism in the cecum ( Lawson, 2015 ), which could be compatible with the overrepresentation we observed for this genus in cecum which is well known to be the main fermenting organ in rabbits.…”
Section: Discussionmentioning
confidence: 82%
“…Little is known about the presence of Anaerofustis (family Eubacteriaceae ) in intestinal communities. Arrazuria et al (2016) found an association between the presence of this genus in cecal samples collected from female rabbits and Mycobacterium avium paratuberculosis infection. Some Anaerofustis species could be involved in the fermentation of carbohydrates and glucose metabolism in the cecum ( Lawson, 2015 ), which could be compatible with the overrepresentation we observed for this genus in cecum which is well known to be the main fermenting organ in rabbits.…”
Section: Discussionmentioning
confidence: 82%
“…A decline of Coprococcus has been demonstrated in patients with intestinal 32 , 33 , neuropsychological 34 , 35 , infectious 36 , and atopic diseases 37 , as well as liver diseases 38 – 40 . A depletion of Dorea has been found in patients with intestinal 41 and infectious diseases 36 , along with liver disease 42 , and a suppression of Anaerostipes has been shown in patients with paratuberculosis infection 43 . In addition, genus Clostridium XI , a SCFA-producing microorganism, within the family Peptostreptococcaceae , was also found to be significantly depleted in the PC group.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors, such as the NOD2CARD15 mutations contributes to risk of developing disease, as these enable the pathogenesis of CD and also have been shown to confer an increased risk to mycobacterial infections [33,34]. MAP itself can further disrupt the biodiversity of the microbial environment of the gut [35], leading to excessive and maladaptive immune responses, which current immune suppressive therapy target. MAP behaviour is similar to other mycobacteria, where there are high infectivity rates but low expression/pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The ability for MAP to influence the gut microbiome has been demonstrated in animal rabbit [35] and cattle [42] models. We propose that the inability to clear MAP from the macrophage and the resulting dysbiosis from viable mycobacteria, leads to granulomas and the relapsing, remitting behaviour observed in CD.…”
Section: Discussionmentioning
confidence: 99%